Nephroprotective activity of medicinal plants: A review on in silico-, in vitro-, and in vivo-based studies - Dani Sujana&, Nyi Mekar Saptarini, Sri Adi Sumiwi, Jutti Levita (Journal of Applied Pharmaceutical Science, 2021)
Acute kidney injury (AKI) is a severe problem for healthcare professionals due to its high mortality rate. The major causes of AKI are ischemia, hypoxia, and drug-induced nephrotoxicity. AKI is particularly related to an imbalance between oxygen and nutrients, which is caused by impaired circulation to the nephrons and increased energy requirements due to oxidative stress. Thus, the concept of using antioxidants to prevent AKI is always interesting to be thoroughly discussed. Many plants have been well recognized for their antioxidant properties, which providentially could work to recover AKI. This review focuses on plants with nephroprotective activity as confirmed by in silico, in vitro, and in vivo studies. In vitro and in vivo nephroprotective studies of several plants on Combretum micranthum, Homonoia riparia, Abelmoschus moschatus, Asparagus falcatus, Barleria prionitis, Macrothelypteris oligophlebia, Solanum xanthocarpum, Sonchus oleraceus, Ceiba pentandra, Eurycoma longifolia, Dendropanax morbifera, Carica papaya, and Boesenbergia rotunda reveal promising results. Moreover, in silico studies of phytoconstituents against nuclear factor κB, the most important components of the pathogenesis of AKI, confirm scientific evidence that plants are potential candidates to be developed as nephroprotective drugs.
Keywords: Acute kidney injury, nephroprotective activity, nuclear factor, kidney injury molecule